2003
DOI: 10.3950/jibiinkoka.106.491
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Psychological Stress in Patients with Facial Palsy

Abstract: Objectives: Facial palsy may cause excessive stress due to the obviousness of its manifestations. We evaluated psychological stress in patients with facial palsy.Subjects and Methods: Subjects were 57 patients, with Bell's palsy, 12 with Ramsay Hunt syndrome, and 11 with zoster sine herpete. Eighteen of 50 questions from the Psychological Stress Response Scale (PSRS) were selected and used to in a questionnaire completed by each patient on 2 separate occasions the first hospital visit and after recovery from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Sugiura et al reported high levels of psychological stress following the onset of facial paralysis, with a decrease in psychological stress as the palsy improved. 48 Alteration of facial appearance can decrease one's image of self and can significantly impact the ability of individuals to interact comfortably in a social setting. In addition, facial deformities that involve scars and cutaneous deformities have a significant negative effect on perceptions of social functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Sugiura et al reported high levels of psychological stress following the onset of facial paralysis, with a decrease in psychological stress as the palsy improved. 48 Alteration of facial appearance can decrease one's image of self and can significantly impact the ability of individuals to interact comfortably in a social setting. In addition, facial deformities that involve scars and cutaneous deformities have a significant negative effect on perceptions of social functionality.…”
Section: Discussionmentioning
confidence: 99%
“…In our Cox proportional hazards model, the recovery rate in the age group between 40 and 59 years was significantly lower than that in the age group of less than 40 years. This result implies that psychologic or physical stress, which is known to increase in middle‐aged people, 13 might delay recovery from Bell's palsy.…”
Section: Discussionmentioning
confidence: 99%
“…Sugiura et al looked at the stress levels of Bell’s palsy patients from initial presentation through full recovery. They found the psychological stress response score of patients with facial palsy to be high on the first hospital visit, suggesting the importance for physicians to treat the psychological aspects of Bell’s palsy [ 16 ]. To help patients work through the mental challenges associated with Bell’s palsy, it is critical that physicians provide recommendations for therapists or emotional guidance during this period.…”
Section: Discussionmentioning
confidence: 99%